Case report: Positioning head tilt observed in a dog and four cats with bilateral peripheral vestibular dysfunction - Tamura, Shinji; Nakamoto, Yuya; Santifort, Koen M.; Tamura, Yumiko (Frontiers in Veterinary Science, 2024)
Positioning head tilt (PHT) is a dynamic neurologic sign that occurs when the head tilts in the opposite side of a voluntary lateral turn of the head. Notably, a head tilt is absent when the head is held stationary or when the animal is moving forward. PHT is thought to be caused by a lack of inhibitory input to the vestibular nuclei due to dysfunction of the cerebellar nodulus and uvula (NU). NU dysfunction is proposed to not only be caused by pathologies that affect the NU itself, but also by reduced input of proprioceptive information from the spindles of cervical muscles. As an example of the former, it has been noted in dogs with hypoplasia of the cerebellar nodulus and uvula (NU), dogs with lysosomal storage diseases, and in a dog with a cerebellar tumor. As an example of the latter, it has been observed in feline cases of hypokalemic myopathy and myasthenia gravis. In this study, we describe and discuss our observations of PHT in one dog and four cats with lesions affecting the peripheral vestibular apparatus bilaterally.